Pengembangan Aplikasi Marketplace Komunitas Sepeda berbasis Android - Haviz Prasetya; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Sport is an activity that becomes a place to channel hobbies, fill spare time, and even become a place to socialize. One of the most popular and easy-to-find sports activities is cycling. Cycling activities are now not only done individually, but many are done in the form of groups, because of this, various bicycle communities have emerged. The emergence of the bicycle community makes it easier for members to exchange information related to bicycles and even buy and sell with each other for spare parts or the bicycle itself. However, the buying and selling process which is considered not to reach a wide range of members requires a forum to handle this problem, so a marketplace to sell all bicycle needs. React Native, Graphql, MongoDB are some of the technologies used in this application.method Waterfall is used as a reference for this application because the elicitation at the beginning has the advantage of maintaining the quality of the system to be built. In the final stage, the system is tested using the whitebox and blackbox to ensure all functions run well